Human Capital, Innovation Capacity and Quality of Economic Growth - Based on Chinese Provincial Panel Data from 2000 to 2013 (Global Journal of Management and Business Research, 2014)
This paper took 30 Chinese provinces, autonomous regions and municipalities directly under the central government as sample and used the provincial panel data from 2000 to 2013, constructed a static and dynamic panel data model, analyzed the relationship among human capital, innovation and the quality of economic growth and came to a conclusion that: ① the first-order lag item of quality of economic growth, the human capital of bachelor degree or above education, innovation, urbanization and industrial structure are positively correlated with the quality of economic growth ② however, the human capital of post-secondary education and marketization are not effective predictor of quality of economic growth in China. Therefore, to positively promote the quality of economic growth in China, duly attention should be paid to human capital investment, innovation promotion, urbanization advancement as well as adjustment of industrial structure.
Keywords: human capital; innovation capacity; quality of economic growth